Cultural ecosystem services trade-offs arising from agriculturization in Argentina : a case study in Mar Chiquita Basin - Auer, Alejandra Denise (2018)
Highlights •We developed a spatial indicator to assess opportunities for recreation and tourism. •We found trade-offs between agricultural commodities and this indicator. •Spatially represented, trade-off was diffuse in the map and small synergy was found. •The trade-off was perceived in terms of the quality losses of places for recreation. •Results support the need to integrate social views with spatial trade off analysis.